ACUTE TOXICITY OF OILY DRILL CUTTINGS ON MANGROVE LITTORAL PERIWINKLE (Pachymelania aurita) OF THE LAGOS LAGOON - IGWEGBE, A.N; AYO-OLALUSI, C.I. (Nigerian Journal of Fisheries, 2020)
Acute toxicity of oily drill cuttings against the littoral mangrove periwinkle (Pachymelania. aurita) of the Lagos Lagoon was evaluated in the laboratory bioassay. 450 specimens of P. aurita were collected from Lagos lagoon and mangrove swamp, put in different holding tanks, half-filled with lagoon water, and aerated. Sand was placed at the bottom of the holding tanks serving as substrate. 20 litres of oily drill cuttings were collected. The bioassays were carried out in glass tanks. The result showed that the acute toxicity of drill mud cuttings based on the immobility response of P. aurita increased with time of exposure. The concentration that caused 50 % immobility in the organisms at 24 hours, 48 hours, 72 hours, and 96 hours was 2057.93 ml/L 394.11 ml/L, 321.85 ml/L, and 122.15 ml/L respectively. The median lethal concentration of drill cuttings and fluids against P. aurita decreased as the duration of exposure increased. There was a significant difference (p< 0.05) between all the treatments at 24, 48, 72, and 96 hours of exposure. There is a need to include bio accumulators such as P. aurita in monitoring programmes to establish the environmental level of drill cuttings in Aquatic Ecosystems.